2022
DOI: 10.3390/cells11091489
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro

Abstract: Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The increased amount of heterochromatin foci in LMNB1 knockdown cells could indicate the need for LMNB1 in melanoma cells to prevent cellular ageing or senescence. To confirm this, we investigated the functional influence of LMNB1 knockdown in MEL-JUSO and SK-MEL-28 cells using established senescence assays [ 37 , 38 ] and revealed an increase in senescent cells as determined by SA β-Gal staining ( Figure 2 A). Furthermore, immunofluorescence staining of the promyelocytic leukaemia protein (PML) expression after LMNB1 knockdown indicated a significant induction of the PML ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The increased amount of heterochromatin foci in LMNB1 knockdown cells could indicate the need for LMNB1 in melanoma cells to prevent cellular ageing or senescence. To confirm this, we investigated the functional influence of LMNB1 knockdown in MEL-JUSO and SK-MEL-28 cells using established senescence assays [ 37 , 38 ] and revealed an increase in senescent cells as determined by SA β-Gal staining ( Figure 2 A). Furthermore, immunofluorescence staining of the promyelocytic leukaemia protein (PML) expression after LMNB1 knockdown indicated a significant induction of the PML ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, we revealed that LMNB1 is downregulated in BRAF V600E - compared to mock-transduced NHEMs ( Figure 3 A). For a proof of concept, we induced senescence in melanoma cells with the cytostatic drug etoposide, which was described previously [ 38 ]. LMNB1 was downregulated in MEL-JUSO and SK-MEL-28 cells treated with etoposide for 48 h ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E , S1E ). We next investigated well-known markers of oncogene-induced senescence [ 28 ] and observed phosphorylation of ERK, hypophosphorylation of Retinoblastoma (Rb) protein and accumulation of histone H3 methylated on lysine 9 upon LPAR1 depletion in HuH7 cells (Fig. 1F ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of melanocyte senescence have been extensively explored in the context of melanoma, particularly BRAF V600E OIS within naevi (moles) [ 22 , 25 , 80 , 81 ]. Although the focus of this review is on the contribution of senescent melanocytes to skin ageing, mechanistic insights can be gained from melanoma research.…”
Section: Melanocyte Senescencementioning
confidence: 99%